Handbook of material weathering - Wypych, George (ChemTec Publishing, 2018)
Handbook of Material Weathering, Sixth Edition, is an essential guide to the effects of weathering on polymers and industrial products, presenting theory, stress factors, methods of weathering and testing and the effects of additives and environmental stress cracking. The book provides graphical illustrations and numerical data to examine the weathering of major polymers and industrial products, including mechanisms of degradation, effect of thermal processes, and characteristic changes in properties. The book also discusses recycling, corrosion and weathering, and the weathering of stone. This sixth edition updates this seminal work with recent developments and the latest data. Polymers and industrial plastics products are widely used in environments where they are vulnerable to the effects of weathering. Weathering stress factors can lead to deterioration or even complete failure. Material durability is therefore vital, and products for outdoor usage or actinic exposure are designed so that the effects of artificial and natural weathering are minimized. This book is an important reference source for those involved in studying material durability, producing materials for outdoor use and actinic exposure, research chemists in the photochemistry field, chemists and material scientists designing new materials, users of manufactured products, those who control the quality of manufactured products and students who want to apply their knowledge to real materials.
Keywords: Materials -- Deterioration -- Handbooks, manuals, etc.; Materials -- Biodegradation -- Handbooks, manuals, etc.; Polymers -- Deterioration -- Handbooks, manuals, etc.; Polymers -- Biodegradation -- Handbooks, manuals, etc.; Environmental testing -- Handbooks, manuals, etc.; Polymers.; elektronické knihy; electronic books